Evaluation of emission indices and air quality implications of liquefied petroleum gas burners. Issue 8 (August 2020) - Oke, Daniel Olawale; Fakinle, Bamidele Sunday; Sonibare, Jacob Ademola; Akeredolu, Funso Alaba
Abstract: Major cities in Nigeria has adopted the use of liquefied petroleum gas (LPG) as their main source for domestic cooking, however, this adoption led to different designs of LPG burners in Nigeria market. The emission indices of these burners and their air quality implications are yet to be ascertain. To solve these problems and fill the data gap, laboratory analysis were carried out on 16 conventional LPG burner heads identified in Nigeria market. The emission factors for Carbon monoxide (CO), Oxide of Nitrogen (NOx), Carbon dioxide (CO2 ), Hydrocarbons (HC) and sulphur dioxide (SO2 ) on the basis of useful energy delivered were 0.123–21.784 g/MJd, 1.973–32.943 g/MJd, 73.819–147.639 g/MJd, 4.069–171.643 g/MJd and 0–0.1644 g/MJd while the emission rates were 0.000238–0.1125 g/s, 0.0071–0.2 g/s, 0.1083–0.7 g/s, 0.0117–1.2583 g/s and 0–0.000194 g/s respectively. It was observed that results from the study were within the International Organization for Standardization, International Workshop Agreement 11 and World Health Organization indoor air quality guidelines for human protection. Abstract : Atmospheric science; Chemical engineering; Environmental analysis; Environmental engineering; Environmental pollution; Mechanical engineering; Indoor air quality; Implications; Emission factors; Emission rates; Useful energy delivered.